Bibliometric Analysis: Collaboration to Optimize Service Capacity to Inland Areas and Logistics Cost Efficiency Through Bundling Strategies and Inter-Port Cooperation - Faris Nofandi; Saut Gurning; Muhammad Saiful Hakim (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Optimizing logistics costs and service capacity is a critical focus in modern supply chain management, particularly for connecting ports to inland